PENERAPAN MODEL PEMBELAJARAN LANGSUNG TERHADAP PENINGKATAN HASIL BELAJAR SERVICE BAWAH PERMAINAN BOLAVOLI (STUDI PADA KELAS VIII SMP NEGERI 1 GLAGAH LAMONGAN) - HEPNI, (Jurnal Pendidikan Olahraga dan Kesehatan, 2013)
Abstract Volleyball game sport that is enjoyed around the world, not only by men only, this time many women has a lot to love this game even be athletes. It can be played by the different walks of life, ranging from the lower classes to the upper classes. However, there are differences in the values ??of basic aspects. One of them is how to perform service right down levels. In this study, researchers wanted to determine the increase of students at the time before and after the service below given direct instruction. Researchers used the study population given the total population of less than 100. So that the research sample in this research is all eighth grade students who totaled 65 students. Data collection techniques in this study by using test and measurement, the variables studied were the results of studying the subject of physical education volleyball. Based on the results of the calculation are known under the services performed by the students had an average standard deviation of 70,36 and 10,89. while the results of the t-test at significance level of 0,05 with degrees of freedom (df) 65-1 = 64 can be seen the value of t-count is greater than t-table value (17,313 > 1,990). Therefore, it can be concluded that Ha was accepted and Ho was rejected. So the application of direct instructional model and influence to improve learning outcomes in service under the volleyball in the eighth grade students of SMP N 1 Glagah. Keywords: Direct Learning Model, Service Down Volleyball.